KEJADIAN HIPEREMESIS GRAVIDARUM DITINJAU DARI RIWAYAT PENGGUNAAN KONTRASEPSI HORMONAL SAAT PRA KONSEPSI DI BPM KUSMAWATI SURABAYA - Yasi Anggasari (Jurnal Ilmiah Kesehatan, 2016)
Event hyperemesis gravidarum viewed from use of history when pre hormonal contraception BPM Kusmawati Surabaya. Nausea vomiting in pregnancy is a physiological state occurs in pregnant women on a trimester 1. But still many pregnant women who experienced nausea vomiting excess accompanied the decline of appetite .The purpose of this research know the incidence of hyperemesis gravidarum seen from the history of the use of hormonal contraception during pre conception in BPM Kusmawati Surabaya. Analytic research design.The population of all pregnant women a trimester 1 visit in BPM Kusmawati Surabaya February 2015 of 22 people , large sample of 21 of respondents.Simple tekhnik random sampling, the independent variable research is the use of hormonal contraceptive and the dependent variable is hyperemesis gravidarum.Instrument of the questionnaire, data processing by means of coding, editing,tabulating and analyzed by test Chi square, with the level of kemaknaan = 0,05 . The results of research most ( 72.7 %) mother who use hormonal contraception had hyperemesis gravidarum. Fisher found the results of the value of statistical test excat =0,008 significance.Significant value < then rejected it means there is the relationship between the use of hormonal contraceptive with hyperemesis gravidarum incident in BPM Kusmawati Surabaya.